The state and the family : the history of population planning in Singapore from 1965-1990 - Peh, Gerald Yong Xiang (Nanyang Technological University, 2022)
Population demographics and population planning have been fundamental aspects of nation-building since the PAP came to power in Singapore. Operating on elitist, eugenicist, and sexist beliefs and under the guise of state survival, the PAP has utilised family and population planning to justify its paternalistic and illiberal rule. This paper seeks to address the following questions: how was population planning used to preserve the ruling party’s cultural and political hegemony, and what were the metanarratives espoused and reinforced through it? This work sets out to answer these questions and examine the history of population planning in Singapore from 1965 to 1990. Additionally, it aims to uncover how categories of class and gender were constructed and defined by the state, and further elaborate how the relationship between the state and the individual has been continually defined by population planning.